Solid Dispersion Formulations by FDM 3D Printing-A Review - Garba M. Khalid; Nashiru Billa (MDPI AG, 2022)
Additive manufacturing (AM) is revolutionizing the way medicines are designed, manufactured, and utilized. Perhaps, AM appears to be ideal for the fit-for-purpose manufacturing of medicines in contrast to the several disadvantages associated with the conventional fit-for-all mass production that accounts for less than 50% of pharmacotherapeutic treatment/management of diseases especially among children and elderly patients, as well as patients with special needs. In this review, we discuss the current trends in the application of additive manufacturing to prepare personalized dosage forms on-demand focusing the attention on the relevance of coupling solid dispersion with FDM 3D printing. Combining the two technologies could offer many advantages such as to improve the solubility, dissolution, and oral bioavailability of poorly soluble drugs in tandem with the concept of precision medicine and personalized dosing and to address the dilemma of commercial availability of FDM filaments loaded with Class II and/or Class IV drugs. However, thermal treatment especially for heat-sensitive drugs, regulatory, and ethical obligations in terms of quality control and quality assurance remain points of concern. Hence, a concerted effort is needed between the scientific community, the pharmaceutical industries, the regulatory agencies, the clinicians and clinical pharmacists, and the end-users to address these concerns.